Dampak Kenaikan Harga Minyak Bumi terhadap Ketersediaan Minyak Goreng Sawit Domestik - Hartoyo, Sri; Putri, Eka Intan Kumala; Novindra, Novindra; Hastuty, Hastuty (UI Scholars Hub, 2011)
This paper attempts to examine the impact of rising fossil fuel prices on the increasing impact on the demand of alternative fuels (biofuels), and its impact on food availability in Indonesia. An econometric model using simultaneous equations is employed. An increase in world crude oil price for 0,192 percent caused the price of real Indonesian palm oil export raised by 10,64 percent. Consequently, a larger biodiesel production is needed to meet their crease of world's consumer demand for biodiesel. Also, with the increase in real export price of Indonesian palm oil, it